CHINA PAKISTAN ECONOMIC CORRIDOR (CPEC): THE COUNTER BALANCER OF MOMENTOUS ENERGY CRISIS IN PAKITAN - Raza, Hasan (Advances in Social Sciences Research Journal, 2018)
This paper will highlight the importance of energy projects that has been covered under the CPEC. Energy is the most important and significant factor for the development and growth of the economy. CPEC is an economic Corridor which is also working as an energy Corridor for Pakistan, 30 billion dollar is invested in energy sector, which will ultimately boost up Pakistan’s shut down industry due to the energy crisis. This paper will highlight the projects of energy sector that has been started in Pakistan and how these energy projects will be beneficial for the economy of Pakistan. This paper will discuss the link between electric power consumption, labor force and price ratio with GDP of Pakistan. Data has been taken from the World Bank for the period of 1990-2016, GDP is considered as dependent variable whereas electric power consumption, labor force and price ratio have been analyzed as independent variables in the light of CPEC and its effects. Least Square Regression has been applied with the help of E-Views a statistical software. The result reveals that GDP of Pakistan is highly and positively affected by electric power consumption, labor force and price ratio. CPEC will help to improve the supply of energy including electricity, increase employment rate and generate more opportunities of employment that will enhance the GDP of Pakistan. The energy projects which includes coal, wind, hydro and solar are covered under the CPEC will help the country to come out from the energy crisis that Pakistan has been facing from the last decade